QUEUE MANAGEMENT SYSTEM - Liaw, Eileen Chuen Ing (Universiti Malaysia Sarawak, (UNIMAS), 2018)
Queue management system is a device to ease customers’ flows by reducing the waiting time and increasing the efficiency of queuing. The current queuing systems at those highly populated compounds such as general hospitals are still focusing more onto conventional method. Customers are required to go to the specified premises in advance to be allowed for a turn after taking the tickets. Hence, it gives rise to the potential of unpredictable waiting time resulting in dissatisfaction from the customers. Therefore, it is very important to reduce time spent on queuing with dependable estimation time and improve the applicable queuing techniques. The proposed queue management system in this project is designed by taking the latest trends of mobile application usage into higher consideration. The number of citizens within all range of ages owning smartphones are also escalated from year to year. Thus, the system proposed made up of a programmed Arduino Uno board as the microcontroller using C++ programming language and compiled in Arduino Software (IDE) to control the flow of customers on mobile queuing. The Arduino Uno is shielded with an ESP8266 Wi-Fi shield and it connects with the Android-based mobile apps developed through a publicly accessible server by using the Internet application. Both Arduino Uno and the mobile apps will communicate by using the server. The main centralized type of queuing is the online queuing that being requested by consumers through their mobile applications on the smartphones. Furthermore, text queuing method implementing through the Short Messaging System (SMS) application is added to increase the reliability of the proposed system and to enhance the queuing efficiency of the users. GSM SIM800L is connected to the Arduino Uno to control the process of sending and receiving texts. The proposed design combines both the wireless and GSM connections thus providing limitless coverage range for the users to access the queue management system.